2012
DOI: 10.5507/bp.2012.022
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound evaluation of fetal gender at 12-14 weeks

Abstract: , Martin Prochazka aAims. The aim of this study was to assess the feasibility and accuracy of fetal gender assignment by transabdominal ultrasound at 12-14 weeks of gestation. Methods. Fetal gender assessment was performed in 1222 singleton pregnancies. In all fetuses the crown-rump length (CRL) was measured and the genital area of the fetus was examined in the mid-sagittal plane. The result of ultrasound examination was compared to the phenotypic sex of the newborn after delivery. Results. The feasibility as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Similarly, numerous previous investigations suggested that correct fetal sex assignment significantly increased with a CRL greater than 55–57 mm and a GA of 12 weeks or greater . Efrat et al reported finding overall accuracy of 100% at CRLs greater than 68 mm, and recently, Lubusky et al reported the same accuracy with CRLs greater than 60 mm.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Similarly, numerous previous investigations suggested that correct fetal sex assignment significantly increased with a CRL greater than 55–57 mm and a GA of 12 weeks or greater . Efrat et al reported finding overall accuracy of 100% at CRLs greater than 68 mm, and recently, Lubusky et al reported the same accuracy with CRLs greater than 60 mm.…”
Section: Discussionmentioning
confidence: 68%
“…We found that a higher maternal BMI was not associated with a lower rate of adequate image acquisition but did influence correct sex determination if the appropriate image was captured. Furthermore, Lubusky et al found that 10% of unassigned cases were undeterminable owing to maternal factors.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the observed fact that the measured genital cusp angle in male fetuses increased with increasing CRL, whereas it did not change signi cantly in female fetuses. Lubusky M. et al (2012) [3] in 1222 patients at 12-14 weeks of singleton pregnancy found a close, directly proportional relationship between CRL increasing with gestational age and the feasibility and accuracy of sex determination. They found that with a CRL of less than 50 mm, corresponding to a pregnancy of less than 11 + 4 weeks, due to an assessment feasibility of 39.1%, with an accuracy of 30.5% (40.9% in males and 24.3% in females), the sex of the foetus could not be reliably predicted.…”
Section: Introductionmentioning
confidence: 99%
“…Improvements in ultrasound systems have allowed over the last few years to see the fetal morphology more clearly, and to detect fetal sex earlier during the first trimester, especially for increasing embryo size, and for male fetuses. 1,2 The early diagnosis of fetal sex during the first trimester of pregnancy, non-invasively and affordably may be important in the diagnosis of sex-linked diseases.…”
Section: Introductionmentioning
confidence: 99%